Wearable technology for holistic entertainment experience - Zhu, Lingfei (2016)
A solution for immersive holistic entertainment system, including the hardware feedback jacket, a Head Mount Device, and a PC game interface. It can interact with the user's head and hand movement or gestures, and provide force feedback with different level of intensity.